Financial Performance Analysis of Food and Beverage Companies in The Listed Food and Beverage Sector on The Indonesia Stock Exchange - Nekky Rahmiyati (Universitas Pendidikan Ganesha, 2022)
This study aims to analyze the impact of the Current Ratio, Debt to Asset Ratio, and Total Asset Turnover on stock prices mediated by Return on Assets in various food and beverage sector companies listed on the Indonesia Stock Exchange from 2017 to 2020. The types of research are quantitative, the number of samples is eight, and the sampling technique is purposive sampling. Multiple linear regressions were used in the analysis and hypothesis testing with the t and F tests. In addition, traditional assumption tests such as normality, multicollinearity, and heteroscedasticity tests were performed. The SPSS 23 for Windows program was used to analyze data in this study. According to the findings of the study, CR and TATO had a positive and significant effect on ROA, DAR had a positive but not significant effect on ROA, CR and TATO had a negative but significant effect on stock prices, DAR had a negative and insignificant effect on stock prices, and ROA had a positive and significant effect on stock prices. Stock Prices, CR, DAR, TATO, and ROA, have a positive and significant effect on ROA; CR, DAR, TATO, and ROA have a positive and significant effect on stock prices; ROA mediates the full mediation effect of CR and TATO on stock prices, and ROA does not mediate the effect of the DAR on share prices in various food and beverage sector companies listed on the Indonesia Stock Exchange.